Implementation Implementation of the TaRL Approach to Increase Student Learning Motivation in Physics Learning: Implementasi Pendekatan TaRL untuk Meningkatkan Motivasi Belajar Peserta Didik pada Pembelajaran Fisika - Budi Juwono; Imam Sucahyo; Melinda Cahya Ningrum Ningrum (UNIB Press, 2023)
This study aimed to increase students' motivation in learning physics by implementing the TaRL (Teaching at The Right Level) approach. This type of research was classroom action research. The research subjects used 1 class X SMA as many as 38 students at SMA Negeri 21 Surabaya. The instruments used were in-class observations and questionnaires on students' learning motivation in learning glasses. The results of the study were that 68.80% of students felt happy during the spectacles learning process with the implementation of the TaRL (Teaching at The Right Level) approach because it was collected according to their respective ability levels and students liked working together in groups to complete the tasks given. From the research that has been carried out, it shows that the TaRL (Teaching at The Right Level) approach can increase students' learning motivation.